KERAWANAN BENCANA TANAH LONGSOR DI WILAYAH HULU DAS JENEBERANG DENGAN ANALISIS GID-3D - Yoenus Osman; Ramli Rahim; Saleh Pallu; Sumbangan Baja (Universitas Fajar, 2016)
The assessment of landslide hazard and risk has become a topic of major interest for both geoscientists and engineering professionals as well as for local communities and administrations in many parts of the world. Recently, Geographic Information Systems (GIS), with their excellent spatial data processing capacity, have attracted great attention in natural disaster assessment. In this paper, an assessment of landslide hazard at Upper Area of Jeneberang Watershed has been studied using GIS technology. By simulating the potential landslide according the minimum safety factor value using GIS, it can be expected that great contribution as a basic decision making for many prevention works before future landslide occurs at Jeneberang River Watershed, South Sulawesi, Indonesia